Anxiety, Depression, and Cigarette Smoking: A Transdiagnostic Vulnerability Framework to Understanding Emotion-Smoking Comorbidity - Leventhal, Adam M. (Psychol Bull, 2014)
Research into the comorbidity between emotional psychopathology and cigarette smoking has often focused upon anxiety and depression’s manifest symptoms and syndromes, with limited theoretical and clinical advancement. This paper presents a novel framework to understanding emotion-smoking comorbidity. We propose that transdiagnostic emotional vulnerabilities—core biobehavioral traits reflecting maladaptive responses to emotional states that underpin multiple types of emotional psychopathology—link various anxiety and depressive psychopathologies to smoking. This framework is applied in a review and synthesis of the empirical literature on three trandiagnostic emotional vulnerabilities implicated in smoking: (1) anhedonia (Anh; diminished pleasure/interest in response to rewards); (2) anxiety sensitivity (AS; fear of anxiety-related sensations); and (3) distress tolerance (DT; ability to withstand distressing states). We conclude that Anh, AS, and DT collectively: (a) underpin multiple emotional psychopathologies; (b) amplify smoking’s anticipated and actual affect enhancing properties and other mechanisms underlying smoking; (c) promote progression across the smoking trajectory (i.e., initiation, escalation/progression, maintenance, cessation/relapse); and (d) are promising targets for smoking intervention. After existing gaps are identified, an integrative model of transdiagnostic processes linking emotional psychopathology to smoking is proposed. The model’s key premise is that Anh amplifies smoking’s anticipated and actual pleasure-enhancing effects, AS amplifies smoking’s anxiolytic effects, and poor DT amplifies smoking’s distress terminating effects. Collectively, these processes augment the reinforcing properties of smoking for individuals with emotional psychopathology to heighten risk of smoking initiation, progression, maintenance, cessation avoidance, and relapse. We conclude by drawing clinical and scientific implications from this framework that may generalize to other comorbidities.